Peptide hydrogelation and cell encapsulation for 3D culture of MCF-7 breast cancer cells - Huang, Hongzhou; Ding, Ying; Sun, Xiuzhi S.; Nguyen, Thu A. (My University, 2013)
Three-dimensional (3D) cell culture plays an invaluable role in tumor biology by providing in vivo like microenviroment and responses to therapeutic agents. Among many established 3D scaffolds, hydrogels demonstrate a distinct property as matrics for 3D cell culture. Most of the existing pre-gel solutions are limited under physiological conditions such as undesirable pH or temperature. Here, we report a peptide hydrogel that shows superior physiological properties as an in vitro matrix for 3D cell culture. The 3D matrix can be accomplished by mixing a self-assembling peptide directly with a cell culture medium without any pH or temperature adjustment. Results of dynamic rheological studies showed that this hydrogel can be delivered multiple times via pipetting without permanently destroying the hydrogel architecture, indicating the deformability and remodeling ability of the hydrogel. Human epithelial cancer cells, MCF-7, are encapsulated homogeneously in the hydrogel matrix during hydrogelation. Compared with two-dimensional (2D) monolayer culture, cells residing in the hydrogel matrix grow as tumor-like clusters in 3D formation. Relevant parameters related to cell morphology, survival, proliferation, and apoptosis were analyzed using MCF-7 cells in 3D hydrogels. Interestingly, treatment of cisplatin, an anti-cancer drug, can cause a significant decrease of cell viability of MCF-7 clusters in hydrogels. The responses to cisplatin were dose- and time-dependent, indicating the potential usage of hydrogels for drug testing. Results of confocal microscopy and Western blotting showed that cells isolated from hydrogels are suitable for downstream proteomic analysis. The results provided evidence that this peptide hydrogel is a promising 3D cell culture material for drug testing.
Keywords: Three-dimensional cell culture; Hydrogels; MCF-7; Drug testing